Rhythm, ancestrality and spirit in Maracatu de Nação and Candomblé: repercussions - Ogle, Lizzie (SOAS studies in music, 2024)
Introduction. Methods and modes of enquiry -- Where the Lion Walks : Leão Coroado, Pathways and Trajectories -- Ground : States of Peripherality, Ecologies of Reciprocity -- Rhythm : Non-linear Histories of Sound, Sensation and Spirit -- Conclusions : Holding History Open.